Quorum Sensing Based Membrane Biofouling Control for Water Treatment: A Review - Muhammad Faisal, Siddiqui; Miles, Rzechowicz; Winters, Harvey; Zularisam, A. W.; G. Fane, Anthony (Elsevier, 2015)
Exploring novel biological strategies to mitigate membrane biofouling is of significant value in order to allow sustainable performance of membrane systems for water and wastewater treatment. Quorum sensing (QS) is a bacterial communication process that involves small diffusible signalling molecules, which activate the expression of myriad genes that control a diverse array of phenotypes such as bioluminescence, virulence, biofilm formation and sporulation. Since QS is often associated with biofilm formation, inhibition of QS should be a promising strategy to control membrane biofouling. Recently, a revolutionary application of bacterial QS has been as a novel strategy for the mitigation of biofouling in membrane systems. In this review an attempt is made to correlate membrane biofouling with QS activity. Moreover, recent trends in membrane biofouling control based on QS are presented and the mechanisms by which different agents mitigate membrane biofouling based on QS are discussed. The potential impact of QS-based methods of biofilm control is assessed. Lastly, brief conclusions and future research challenges in membrane biofouling control based on QS are highlighted.